Perceived service quality and student satisfaction: a case study at Khoja Akhmet Yassawi University, Kazakhstan - Seitova, Meruyert; Temirbekova, Zhanar; Kazykhankyzy, Lazura; Khalmatova, Ziyoda; Çelik, H. Eray (Frontiers in Education, 2024)
The higher education sector is a dynamic and competitive environment where service quality plays a crucial role. Higher education institutions must continuously enhance their service quality in the current competitive landscape. This quantitative study examines perceived service quality’s effect on student satisfaction at Khoja Akhmet Yassawi University in Kazakhstan. The study data were collected with SERVQUAL, and Covariance Structural Equation Modeling (CB-SEM) was employed to test the research hypotheses. The CB-SEM findings confirmed the impact of perceived service quality on student satisfaction. It was found that students were generally satisfied with the university facilities. The findings could assist the university, and by extension, the entire higher education industry, in improving its strategic plans to increase student satisfaction and overall institutional performance. Thus, service quality significantly impacts student satisfaction in higher education, and higher education institutions, including yours, should be aware of the dimensions of service quality that affect student satisfaction.